Clinical Characteristics and Risk Factors for Severe Disease of Coronavirus Disease 2019 in a Low Case Fatality Rate Region in Korea - Kim, Misun; Yoo, Jeong Rae; Heo, Sang Taek; Lee, Hyang Ran; Oh, Hyunjoo (Infection & chemotherapy, 2021)
Jeju island had the seventh highest incidence rate of coronavirus disease 2019 (COVID-19) but showed the lowest case fatality rate among 17 provinces of Korea, which may be associated with comorbidities and geographic differences. This study aimed to analyze the epidemiological and clinical characteristics of patients with COVID-19 and evaluate the risk factors for severe COVID-19 in Jeju island, Korea. All patients with COVID-19 admitted between February 20, 2020, and June 19, 2021, at a single center were retrospectively enrolled in this study. The severity of illness was defined using five categories (asymptomatic, mild, moderate, severe, and critical) according to the National Institute of Health criteria. Then, patients with severe and critical illness were grouped into a severe group, whereas patients with asymptomatic, mild, and moderate illness were grouped into a non-severe group. Multivariate logistic regression analysis was performed using risk factors that were found to be significantly associated with the severe group. This study included 348 patients with a median age was 57 years, and 37.5% were aged 60 or older. Among them, 43.4% were male and 10.9% were asymptomatic, whereas 41.4%, 33.9%, 12.9%, and 1.1% had mild, moderate, severe, and critical illness. The all-cause mortality of patients with COVID-19 was 0.28% (1/348). Among confirmed patients with COVID-19, exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was mainly within Jeju island (75.9%). The mean body mass index was 24.09 ± 4.04 kg/m², the median comorbidity index score was low in each group (0 in asymptomatic; 1 in mild; 1 in moderate; 1 in severe; and 2 in critical group, <0.548). In the multivariable analysis, male sex [odds ratio (OR), 6.37; 95% confidence interval (CI), 2.69 - 15.13; <0.001], ≥65 years of age (OR, 2.68; 95% CI, 1.18 - 6.10; <0.019), chronic pulmonary disease (OR, 6.10; 95% CI, 1.40 - 26.61; = 0.016), and length of fever duration (OR, 1.33; 95% CI, 1.19 - 1.49; <0.001) were independently associated with severe COVID-19. The most relevant risk factors of COVID-19 severity were male sex, older age, underlying chronic lung diseases, and duration of fever during hospitalization. The risk factors for severe COVID-19 were not significantly different from those reported in other studies. However, a lower proportion of the older population among confirmed SARS-CoV-2 cases might contribute to the lower fatality rate than the national rate.